1998
DOI: 10.1038/sj.leu.2400984
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in multiple myeloma: cyclosporin A analogues and their metabolites as potential chemosensitizers

Abstract: In vivo, cyclosporins are rapidly and almost completely converted to metabolites. AM1 and AM4N, primary metabolites of CsA, mediated inhibition of transport, as did CsG metabolites GM1, GM4N and GM9. AM1 and GM9 are known to reach steady-state in vivo levels that exceed the inhibitory concentration identified here by 1.1-to 1.9-fold. Thus, cyclosporin metabolites, which accumulate in the blood during infusion of CsA and other cyclosporins, are shown here to be effective chemosensitizers for normally drugresist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…For example, the inhibition of the mammalian target of rapaymycin/Akt pathway has been associated with an anti-tumor effect in MM cells treated with pomalidomide [41]. Mycophenolate mofetil has an anti-proliferative effect on MM in vitro [42], and cyclosporine may sensitize MMs tumoral cells to chemotherapy in vitro [43]. Nevertheless, these results are not sufficient to form a conclusion about the effects of immunosuppressive therapy on PCN in vivo in KT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the inhibition of the mammalian target of rapaymycin/Akt pathway has been associated with an anti-tumor effect in MM cells treated with pomalidomide [41]. Mycophenolate mofetil has an anti-proliferative effect on MM in vitro [42], and cyclosporine may sensitize MMs tumoral cells to chemotherapy in vitro [43]. Nevertheless, these results are not sufficient to form a conclusion about the effects of immunosuppressive therapy on PCN in vivo in KT.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, MDR 1 is only one of several mechanisms through which myeloma patients may become refractory to chemotherapy (Gieseler & Nussler, 1998;Raaijmakers et al, 1998;Sonneveld, 1999). The question remains whether a benefit by MDR 1 reversal may be expected early during the disease, when the frequency of MDR 1 and other resistance pathways may still be low, as opposed to highly refractory patients who have no other treatment options left (Futscher et al, 1996;Pilarski et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Using intracellular accumulation of calcein, daunorubicin and vincristine as a marker for P-gp inhibition, we screened more than 800 plant extracts that are available in Korea and China and selected 8 for further investigation: Aloe ferox, Caesalpinia sappon, Dalbergia odorifera, Curcuma zedoariae rhizome, Zanthoxylum planisinum, Ageratum conyzoides, Curcuma aromatica and Culcuma longa. We also examined the effect of 3 herbal constituents, curcumin, quercetin and flavones, which are abundant in the extracts (Pilarski et al, 1998) and are reported to inhibit P-gp (Choi et al, 2004a;Choi et al, 2004b;Shin et al, 2006;Limtrakul, 2007;Pilarski et al, 1998). Since calcein, daunorubicin and vincristine, P-gp substrates used in the present study, are also substrates for MRP1 (Essodaigui et al, 1998;Renes et al, 1999;Versantvoort et al, 1994), the involvement of endogenous transporters (e.g.…”
Section: Discussionmentioning
confidence: 97%